PSA testing for men at average risk of prostate cancer - Bruce K Armstrong; Michael J Barry; Mark Frydenberg; Robert A Gardiner; Ian Haines; Stacy M Carter (Sax Institute, 2017)
Prostate-specific antigen (PSA) testing of men at normal risk of prostate cancer is one of the most contested issues in cancer screening. There is no formal screening program, but testing is common - arguably a practice that ran ahead of the evidence. Public and professional communication about PSA screening has been highly varied and potentially confusing for practitioners and patients alike. There has been much research and policy activity relating to PSA testing in recent years. Landmark randomised controlled trials have been reported; authorities - including the 2013 Prostate Cancer World Congress, the Prostate Cancer Foundation of Australia, Cancer Council Australia, and the National Health and Medical Research Council - have made or endorsed public statements and/or issued clinical practice guidelines; and the US Preventive Services Task Force is revising its recommendations. But disagreement continues. The contention is partly over what the new evidence means. It is also a result of different valuing and prioritisation of outcomes that are hard to compare: prostate cancer deaths prevented (a small and disputed number); prevention of metastatic disease (somewhat more common); and side-effects of treatment such as incontinence, impotence and bowel trouble (more common again). A sizeable proportion of men diagnosed through PSA testing (somewhere between 20% and 50%) would never have had prostate cancer symptoms sufficient to prompt investigation; many of these men are older, with competing comorbidities. It is a complex picture. Below are four viewpoints from expert participants in the evolving debate, commissioned for this cancer screening themed issue of Public Health Research & Practice. We asked the authors to respond to the challenge of PSA testing of asymptomatic, normal-risk men. They raise important considerations: uncertainty, harms, the trustworthiness and interpretation of the evidence, cost (e.g. of using multiparametric magnetic resonance imaging to triage patients with elevated PSA), a likely bias towards intervention (particularly for cancer), and the potential to limit harm by treating more conservatively (although this may not occur consistently). They provide important insights, and disagree on some issues, but generally concur that men should decide for themselves whether to be tested. It seems reasonable to support men's autonomy to make their own decisions based on their own values. However, the support men might require to decide is likely to be considerable, and this needs to be taken seriously in policy making.